Stochastic optimization models in forest planning: a progressive hedging solution approach - Veliz, Fernando Badilla; Watson, Jean-Paul; Weintraub, Andres; Wets, Roger J.-B.; Woodruff, David L. (Annals of operations research, 2015)
We consider the important problem of medium term forest planning with an integrated approach considering both harvesting and road construction decisions in the presence of uncertainty modeled as a multi-stage problem. We give strengthening methods that enable the solution of problems with many more scenarios than previously reported in the literature. Furthermore, we demonstrate that a scenario-based decomposition method (Progressive Hedging) is competitive with direct solution of the extensive form, even on a serial computer. Computational results based on a real-world example are presented.